The role of non-technical skills in surgery. Issue 4 (December 2015) - Agha, Riaz A.; Fowler, Alexander J.; Sevdalis, Nick
Abstract: Non-technical skills are of increasing importance in surgery and surgical training. A traditional focus on technical skills acquisition and competence is no longer enough for the delivery of a modern, safe surgical practice. This review discusses the importance of non-technical skills and the values that underpin successful modern surgical practice. This narrative review used a number of sources including written and online, there was no specific search strategy of defined databases. Modern surgical practice requires; technical and non-technical skills, evidence-based practice, an emphasis on lifelong learning, monitoring of outcomes and a supportive institutional and health service framework. Finally these requirements need to be combined with a number of personal and professional values including integrity, professionalism and compassionate, patient-centred care. Highlights: The volume of surgical procedures is increasing. Technical skills have come under increased scrutiny, alongside a realisation of the importance of non-technical skills. Non-technical skills include situational awareness, decision making, communication, teamwork and leadership. Further research is required to demonstrate the mechanism linking impaired non-technical skills and patient harm.